(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2022)
The essay aims to reconstruct the history of Manzoni’s Versi improvvisati sopra il nome di Maria through new documents and new witnesses. This short poem was first published by Ruggiero Bonghi in 1883 according to a copy that belonged to Gaetano Giudici. In 1922 Michele Scherillo provided a new edition with variants, on the basis of a new copy that was considered lost until now. The text given by Scherillo was accepted by Ghisalberti in 1957, therefore by all later publishers. Today, the manuscript that belonged to Scherillo has been found. It casts serious doubts on the publisher’s behavior, therefore on the most widespread form of the text.